Esthetic Parameters in Prosthodontic Practice - Margvelashvili-Malament, Mariam (Caucasus Journal of Health Sciences and Public Health, 2020)
Restorations in the esthetic zone can be very challenging. The webinar intends to review inter-disciplinary approach of comprehensive care in the esthetic zones. First, basic principles and landmarks of esthetic parameters will be presented. It will then focus on how the dento-alveolar changes relate to the facial changes, and what is the checklist for the inter-disciplinary group to evaluate and envision prior to starting a treatment plan. The webinar will also discuss the clinical cases and how to apply the reviewed esthetic parameters to the natural abutments. At the end, the webinar will focus on the implant supported fixed restorations in theanterior areas. Biologic characteristics of the peri-implant soft tissues and the ways to evaluate and diagnose anterior esthetic implant sites for achieving more predictable outcomes will be discussed. Crown and abutment complexes and their indications, along with how to prosthetically deal with various compromised sites will be reviewed. Together with single implant sites, larger anterior inter-disciplinary edentulous areas will be presented.